Multimicronutrient supplementation in older persons decreased zinc deficiency but not serum TNF-ï¡ - Herwana, Elly; Yenny, Yenny (Universa Medicina, 2011)
The increase in the population of older persons needs to be accompanied by increased quality of healthcare in older persons, particularly a decrease in the incidence of infections. Impaired immune responses are common in older adults, and immune senescence likely contributes to the increased incidence of infectious diseases in the older persons. The aging process decreases the immune response and many studies have been conducted to explain the role of supplementation with various micronutrients, such as vitamin C, vitamin E, â-carotene and zinc, on the immune response. The aim of the present study was to assess the influence of 6 months of multi-micronutrient (MMN) supplementation on zinc and tumor necrosis factor (TNF-á) levels in older persons. A randomized controlled trial was conducted on 78 older persons, who were divided into two groups. The treatment group received MMN supplementation containing 40 mg elemental zinc, 120 mg ascorbic acid, 6 mg â-carotene, 15 mg á-tocopherol and 400 ìg folic acid and the control group 400 mg calcium carbonate. The study did not demonstrate that 6 months of MMN supplementation resulted in significant differences between both groups, with respect to total protein, albumin, globulin, and TNF-á levels. In contrast, MMN supplementation significantly decreased the proportion of older persons with zinc deficiency in the treatment group, in comparison with the control group. The present data suggest that in older persons with relatively good immune and protein status, improvement of the immune status by MMN supplementation may be difficult and at best limited.